The Link Between Energy-Related Sensations and Metabolism: Implications for Treating Fatigue - Filippi, Marco; Krähenmann, Rainer; Fissler, Patrick (Frontiers in Psychology, 2022)
Energy-related sensations include sensation of energy and fatigue as well as subjective energizability and fatigability. First, we introduce interdisciplinary useful definitions of all constructs and review findings regarding the question of whether sensations of fatigue and energy are two separate constructs or two ends of a single dimension. Second, we describe different components of the bodily energy metabolism system (e.g., mitochondria; autonomic nervous system). Third, we review the link between sensation of fatigue and different components of energy metabolism. Finally, we present an overview of different treatments shown to affect both energy-related sensations and metabolism before outlining future research perspectives.